Caracterización Operacional y de Mantenimiento de la Flota de Cargadores Cat-990 en Servicio ubicados en una Mina de la Región Caribe. - Jiménez Meza, Oscar Alfredo (Boletín de Innovación, Logística y Operaciones, 2021)
This article shows the results of the research in which the RCM 2 methodology was applied, whose purpose was to establish the operational context, the list of functions and the determination of critical systems by applying a criticality analysis to the fleet of CAT-loaders. 990 in service, located in a mine in the Caribbean region. This work was developed to opt for operational improvement in the logistics area of the research mining company. Through this article, the importance of maintenance and business logistics as a technological tool for the improvement of production processes is highlighted, which goes beyond the simple monitoring imposed by conventional control techniques, without detracting from them as useful tools to control their performance.